Bitter taste perception and TAS2R38 genotype: effects on taste sensitivity, food consumption and anthropometry in Mexican adults. (28th March 2016) - Barajas‐Ramírez, Jahir A.; Quintana‐Castro, Rodolfo; Oliart‐Ros, Rosa M.; Angulo-Guerrero, Ofelia
Abstract: Differences in sensitivity to 6‐ n ‐propylthiouracil (PROP) are associated with TAS2R38 genotypes. Those differences allow the classification in "nontasters" (NT), "tasters" (MT) and "supertasters" (ST), which have been related to differences in taste acuity and nutritional status, although there is controversy in the results obtained by different research groups. The aim of this study was to determine the frequencies of NT, MT and ST, TAS2R38 genotypes and to analyze its relationship with taste sensitivity, food consumption and anthropometric measures in healthy Mexican adults. Body Mass Index (BMI), Waist Circumference (WC), TAS2R38 genotype, detection thresholds for sucrose, capsaicin, PROP and linoleic acid as well as intensity perceived for sucrose, capsaicin and PROP suprathreshold solutions were performed in 76 Mexican adults. Food restriction was assessed and two seven‐day food consumption records from 66 individuals were analyzed. The proportion of subjects with genotype AVI/AVI, and its associated phenotype NT, was close to 10%; the proportion of MT and ST was 54.6 and 31.8 respectively. Genotypes associated with ST were present in 38%, while those associated with MT accounted for 41% of the population. PROP sensitivity was associated with linoleic acid sensitivity, consumption of vegetables, grains and dairy foods. BMI and WC were negatively correlated to carbohydrate intake and linoleic acid detection threshold. PROP taster status and TAS2R38 genotypes were related. PROP and linoleic acid sensitivity influences food consumption in unrestrained eaters and could produce differences in long‐term nutritional status. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : PROP and linoleic acid sensitivity influences food consumption which could produce differences in the long‐term nutritional status.